2019
DOI: 10.35631/ijmtss.210001
|View full text |Cite
|
Sign up to set email alerts
|

Vark Learning Styles Towards Academic Performance Among Students of Private University in Selangor

Abstract: The objectives of this study are twofold: (a) to examine the influence of students’ learning styles on their academic performance; and (b) to identifies the preferred learning styles of students between high/low achievers, gender, and different clusters. By using VARK standard questionnaire, 433 undergraduate students from four faculties at the Private University in Selangor are used as observations for this study. The study finds that all students were unimodal learners and Kinesthetic (K) type of learning st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It was seen that the e-learning styles and educational technology standards of the teacher candidates are related to their academic achievement. Zain, et al, (2019) stated that learning environments should be designed according to students' dominant learning styles so that students can perform better. Akturk& Ozturk (2019) states that teachers' techno-pedagogical field levels and students' academic, social and emotional self-efficacy explain 12% of students' academic success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was seen that the e-learning styles and educational technology standards of the teacher candidates are related to their academic achievement. Zain, et al, (2019) stated that learning environments should be designed according to students' dominant learning styles so that students can perform better. Akturk& Ozturk (2019) states that teachers' techno-pedagogical field levels and students' academic, social and emotional self-efficacy explain 12% of students' academic success.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that there is a connection between the learning styles of individuals and their success levels of their lessons (Alsan&Alsan, 2009;Sapanci, 2014;Wilkinson et. al., 2014;Zain et. al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Albeta et al [18] found that visual and kinesthetic learning styles have lower performance than aural learning styles. In comparison, Zain et al [10] concluded that students who obtained high academic scores were those who used kinesthetic learning styles based on their research on students in Selangor. The results differences are most likely due to differences in external factors that affect student learning styles, such as geographic location, learning environment, characteristics of the research subject itself, and many other factors.…”
Section: The Relationship Between Learning Style and Academic Achieve...mentioning
confidence: 99%
“…For example, research results from [7] found that the audio-visual learning style is the most effective in improving students' academic achievement. Meanwhile, [10] found that the most effective learning style to improve students' academic achievement is the Kinesthetic (K) learning style. From the two research results mentioned above, our research results differ in the most effective learning style and the quantity of learning styles that each student adopts.…”
Section: Introductionmentioning
confidence: 99%
“…This is because it does not address certain important parameters, for example level of interest and motivation, learners' socioeconomic status race and culture. 11,12 Many studies have used the VARK questionnaire to determine students learning preference. The results from these studies show a various variance and lie on both ends of the spectrum.…”
Section: Original Articlementioning
confidence: 99%